IDENTIFIKASI KESEGARAN IKAN - Alfi Yusril Auliya (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2021)
The purpose of making it is for students to understand the freshness of fish, be able to distinguish the stages of decay of aquatic committees, and identify the level of freshness of fish. Fresh fish is very influential in buying and selling, so it really must be paid attention to its freshness for sale or processing